Identification of the regulatory roles of water qualities on the spatio-temporal dynamics of microbiota communities in the water and fish guts in the Heilongjiang River - Jin, Hongyu; Li, Lei; Lu, Wanqiao; Zhang, Zepeng; Xing, Yue; Wu, Di (Frontiers in Microbiology, 2024)
In the present study, the water samples and fish guts were collected from four locations of Heilongjiang River during both dry season and wet season, in order to analyse the spatio-temporal dynamics of microbiota communities in the water environment and fish guts through performing the 16s ribosome RNA sequencing. The water qualities showed seasonal changes, of which the pH value, dissolved oxygen, and total dissolved solids were generally higher during dry season, and water temperature was higher during wet season. RDA indicated that higher pH value, dissolved oxygen, and total dissolved solids promoted the formation of microbiota communities in the water samples of dry season, while higher water temperature positively regulated the formation of microbiota communities in the water samples of wet season. LEFSe identified 5 biomarkers with the most abundant difference at genus level, of which TM7a was up-regulated in the water samples of dry season, and SM1A02, Rheinheimera, Gemmatimonas, and Vogesella were up-regulated in the water samples of wet season. Pearson analysis revealed that higher pH value and dissolved oxygen positively regulated the formation of TM7a, and negatively regulated the formation of SM1A02, Rheinheimera, Gemmatimonas, and Vogesella (p < 0.05), while higher water temperature has the opposite regulatory roles on the formation of these biomarkers. The relative abundance of microbiota diversity in fish guts varies greatly between different fish species, even the fishes were collected from the same water source, indicating dietary habits and fish species may be the key factors, affecting the formation and construction of microbiome community in fish gut.P. glenii, P. lagowskii, G. cynocephalus, and L. waleckii were the main fish resources, which were collected and identified from at least six sample points. RDA indicated that the microbiota in the water environment regulated the formation of microbiota community in the guts of G. cynocephalus and L. waleckii, while has limited regulated effects on P. glenii and P. lagowskii.The present study identified the regulatory effects of water qualities on the formation of microbiota community in the water samples and fish guts, providing valuable evidences for the protection of fish resource in Heilongjiang River.